Analisis vertical del estado de situación financiera de la unidad de hemodiálisis del cantón ventanas, provincia de los ríos en el periodo 2021-2022. - Villamar León, Edgar Enrique (2023)
The analysis of financial statements constitutes a fundamental tool in all business activity, regardless of whether the company is large, medium or small, and regardless of the activity carried out, evaluating financial performance over time allows comparing the values obtained and helps to identify trends, strengths and weaknesses of the financial situation. Adequate monitoring and control of the company's financial situation will allow, where appropriate, to take the necessary corrective measures in time and execute action plans that allow sustainability over time. By using vertical analysis, it is possible to identify which accounts or items represent a greater or lesser proportion of the total, being especially useful for detecting deviations or anomalies in the financial statements. To complement the development of this research, the financial indicators corresponding to the case were also calculated and interpreted, with the aim of obtaining an overview as close as possible to the real situation of the company